An assessment of the Australian V4 strain of Newcastle disease virus as a vaccine by spray, aerosol and drinking water administration - Ibrahim, Abdul Latif; Ungku Mohsin, Mohd. Ungku Chulan; Babjee, Ahmad Mustaffa (Australian Veterinary Association, 1981)
An Australian strain of Newcastle disease virus, was evaluated for use as a vaccine following its administration by drinking water, aerosol and spray to chickens at 1 and 21 days of age. Haemagglutination inhbition antibody was produced and persisted for 11 weeks. Aerosol vaccination induced higher levels of haemagglutination inhibition antibody than the other methods of vaccination. No respiratory disease was observed following vaccination. Chickens vaccinated by aerosol and spray were fully protected when challenged at 5, 7 and 11 weeks of age with virulent Newcastle disease virus. Mortality of 10 to 30 per cent was observed in chickens vaccinated by drinking water and intranasally following challenge.